Evaluation and characterisation of Chronic myeloid leukemia and various treatments in Saudi Arabia: A retrospective study - Farjah H. Algahtani; Fatmah S. Alqahtany (Elsevier, 2020)
Background: Chronic myeloid leukemia (CML) is a clonal BCR-ABL1-positive myelo-proliferative disorder resulting from an acquired genetic mutation, characterized by the presence of the Philadelphia (Ph) chromosome. CML is associated with significantly high granulocyte numbers in the bone marrow and peripheral blood. Materials and Methods: This retrospective study conducted at the Hematology Unit of King Saud University Medical City aimed to evaluate the incidence and characteristics of CML and the various treatments in Saudi Arabia. We have evaluated the demographic, clinical, and hematological data of 56 consecutive patients who visited the hospital from Jan 2012 to Jan 2018. Results: The diagnosis and stage of CML were determined based on the World Health Organization criteria, following polymerase chain reaction analysis of bone marrow aspirates. Our study group had equal numbers of genders with a age mean of 43.3 + 18.1 years. The predominance of younger patients and equal incidence in males and females could be due to the racial and socioeconomic disparities among our patients compared to those in previous studies. While the most predominant symptom was fatigue and bone pain, the most common clinical sign was hepato-splenomegaly, followed by remarkable weight loss, and epistaxis. Conclusion: A patient with an increased WBC count, abdominal pain, left side distension, and hepato-splenomegaly should clearly be evaluated for CML. Keywords: Chronic myeloid leukemia, Imatinib, Philadelphia chromosome